KAJIAN HUBUNGAN AGAMA DAN NEGARA DALAM PERSPEKTIF HIZBUT TAHRIR - Losi, Zainuddin; Rahim, Andi Rahmawan; Dalif, Dalif (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
Hizbut-Tahir (HT) claims Islam as the only paradigm in all its activities and ideas. This is certainly contrary to the secular paradigm that currently dominates the world. This paper aims to identify both the HT concept of relation between religion and state and its method to apply its perspectives in that relation. The results show that within HT perspective, the relation between religion and state is integrated by which Islam and state must be united. This perspective is unquestionably exposed within the three intermingling concepts of HT; Islam, Islamic state, and caliphate. In its effort to re-establish the structure of caliphate (khilafah), HT boasts three stages of integrating religion and state by firstly recruiting and educating cadres (Tahapan Pengkaderan), followed by the stage of interaction with the community (Tahapan Interaksi dengan Masyarakat), and lastly by accepting power (Tahapan Penerimaan Kekuasaan).